Hierarchically Porous and Nitrogen‐Doped Graphene‐Like Microspheres as Stable Anodes for Lithium‐Ion Batteries. Issue 11 (23rd July 2015) - Sun, Dongfei; Yan, Xingbin; Yang, Juan; Zhang, Peng; Xue, Qunji
Abstract: Novel 3D hierarchically porous and nitrogen‐doped graphene‐like microspheres (3D NPGSs) are prepared by precursor‐assisted chemical vapor deposition. 3D NPGSs obtained by using Ni microspheres as a structural template exhibit a 3D conductive framework, and have a well‐defined porous structure, large surface area and appropriate heteroatom doping, making them suitable for high‐performance storage of lithium ions. Consequently, a good rate capability and excellent cycle performance are achieved using the 3D NPGSs as anodes for lithium storage, and a high reversible capacity of 840 mA h g −1 is obtained after 200 cycles. For a further capacitance boost, a thin layer of iron oxide nanoparticles is deposited onto the 3D NPGSs. The resulting 3D FeO x –NPGS electrode exhibits a stable reversible capacity up to 1343 mA h g −1 after 100 cycles. Abstract : Battery LiFe : Hierarchically porous and nitrogen‐doped graphene microspheres (3D NPGSs) are prepared by precursor‐assisted chemical vapor deposition. The NPGSs and 3D FeO x –NPGS electrodes both display high capacity and excellent cycling stability in lithium‐ion batteries.